Quartz-bearing C-O-H fluid inclusions diamond: Retracing the pressure-temperature path in the mantle using calibrated high temperature IR spectroscopy - Tomlinson, Emma (My University, 2007)
Infrared spectra of C–O–H micro-inclusions were collected from a micro-inclusion bearing diamond during step-heating and freezing experiments to examine fluid speciation as a function of pressure and temperature. The inclusions contain H2O, CO2, carbonate, apatite, quartz and mica, which together represent the oxidising remnant mantle fluid composition after diamond crystallisation. The internal pressure of the inclusions, measured from calibrated shifts of the quartz peaks, increases from 1.3 GPa at ambient temperature, to approximately 4–5 GPa at 737 °C, close to the conditions of crystallisation of the host diamond in the mantle.
PUBLISHED
Keywords: Diamond; C–O–H micro-inclusions; Mantle fluids